2014
DOI: 10.1186/1471-2164-15-638
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Homeobox C11 protein in water buffalo Bubalus bubalis and its putative 3D structure

Abstract: BackgroundThe Homeobox (Hox) family complex contains 39 genes, clustered into four groups (A-D) all expressing in sequential manner. The HOX proteins are transcriptional factors involved in regulation of pattern formation of the anterio-posterior body axis across the species. Most of the Hox family genes have been studied with respect to their organization and expression during the embryonic stages. However, expression pattern of Homeobox C11 (Hoxc11) gene in the 5′ region, particularly in higher mammals remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In a recent study, from our laboratory, we localized the HOXC11 protein in the nuclei of gonads and different somatic tissues of buffalo employing immunohistochemistry. Subsequently, immunoblotting using specific antibodies showed differential expression of buffalo HOXC11 protein reflecting its possible tissue-specific function (Sharma et al, 2014). In the present study, we have demonstrated varying levels of Hoxc11 gene expression in an adult buffalo.…”
Section: Discussionsupporting
confidence: 54%
“…In a recent study, from our laboratory, we localized the HOXC11 protein in the nuclei of gonads and different somatic tissues of buffalo employing immunohistochemistry. Subsequently, immunoblotting using specific antibodies showed differential expression of buffalo HOXC11 protein reflecting its possible tissue-specific function (Sharma et al, 2014). In the present study, we have demonstrated varying levels of Hoxc11 gene expression in an adult buffalo.…”
Section: Discussionsupporting
confidence: 54%
“…Total RNA was isolated from the ovary following standard protocols and stored at—80°C, quality and integrity of RNA was tested on 1% formaldehyde agarose gel [ 20 ]. Further, RNA was quantified using a NanoDrop (ND-1000 Spectrophotometer, Thermo Fisher Scientific, USA) and tested for genomic DNA presence with β-actin primers ( ACTB ) (forward: and reverse: ).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR reaction conditions involved initial denaturation at 95°C for 3 minutes, followed by 35 cycles each with a subsequent denaturation at 95°C for 1 minute, annealing at 52.0°C ( KGF ) and 54.0°C ( KITLG ) for 1.5 minutes and extension at 72°C for 2 minutes followed by a final extension at 72°C for 10 minutes. Each PCR product was electrophoresed on 1% agarose gel in 1x TAE buffer, sliced and DNA was eluted using gel extraction kit (Qiagen, Germany) [ 20 ]. Subsequently, eluted DNA fragments corresponding to KGF and KITLG were cloned between the respective restriction enzyme sites of His-tagged pET28a (Novagen, USA) and GST-tagged pGEX-4T1 (Amersham Bioscience) vectors, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Screening for the positive clones were done by colony-PCR. The recombinant clones were then sequenced on 3130xl genetic analyzer using BigDye® Terminator v3.1 cycle sequencing kits (Applied Biosystems, USA) [33]. Then the deduced mRNA sequences of BuLA-DMα and DMβ genes were submitted to the NCBI database and their corresponding accession numbers were obtained.…”
Section: Methodsmentioning
confidence: 99%